Digitalisasi Sebagai Upaya Peningkatan Kepatuhan Penggunaan Obat Pasien Tuberkulosis: Studi Literatur - Kartikawati, Nurfina Dian; Febriani, Anisa Putri; Rizki, Rahmania Hafidhotur; Sari, Lutfiana (Borobudur Pharmacy Review, 2024)
Patient adherence to TB treatment regimen is essential to ensure recovery and prevent drug resistance. The use of drug reminder applications in the management of Tuberculosis (TB) is increasingly growing in the digital era. This literature aims to review the effect of drug reminder applications on TB patient adherence. The method used is a systematic literature review by searching various relevant scientific databases, such as Crossref and Google Scholar, for articles published in the last two years. The keywords in this study are: Tuberculosis; Drug Adherence; Drug Reminder Application. The literature search was conducted by combining Boolean search terms ("AND", "OR"). In 6 articles, the results of the literature showed that the use of drug reminder applications has a positive impact on patient adherence, with several studies showing an increase in adherence of up to 30%. Factors such as ease of use, daily reminder features, and support from health workers determine the success of the application. The main conclusion of this study is that digitalization of drug reminder applications has the potential to be an effective solution in improving TB patient adherence, but further research is needed to evaluate the sustainability of its impact in the long term.